Natural convective flow past a suddenly started vertical plate with uniform mass and heat flux in the presence of radiation, thermal diffusion. Issue 6 (5th May 2022) - Bormudoi, Mridusmita; Ahmed, Nazibuddin; Bordoloi, Rajdeep
Abstract: An attempt has been made to investigate the problem of a natural convective radiative flow past an impulsively moving vertical plate with uniform mass and heat flux in the existence of the thermal diffusion effect. The resulting governing equations are solved by the Laplace transform technique in closed form. Effects of radiation, Prandtl number, Soret number, Grashof number, modified Grashof number, and Schmidt number are studied on temperature field, concentration field, velocity field, plate temperature, plate concentration, skin friction, and are demonstrated through graphs. The present study reveals that an intensification of the thermal radiation effect causes a downfall in the fluid temperature, plate temperature, and skin friction, but a contradictory outcome is spotted for plate concentration. One of the significant findings of this study includes that the increasing thermo‐diffusion effect hikes the concentration and frictional resistance of the field.